Retention time of chlorophacinone in black‐tailed prairie dogs informs secondary hazards from a prairie dog rodenticide bait. Issue 4 (18th June 2015) - Witmer, Gary W; Snow, Nathan P; Moulton, Rachael S
Abstract: BACKGROUND: Secondary toxicity in mammals and birds that consume animals containing residues of anticoagulant rodenticides represents a persistent conflict between conservation, agriculture and environmental contamination. Chlorophacinone residues in black‐tailed prairie dogs ( Cynomys ludovicianus ) represent a secondary exposure hazard to predatory and scavenging avian and mammalian species in the Central Plains of the United States, especially considering efforts to re‐establish black‐footed ferrets ( Mustela nigripes ). Rozol ® Prairie Dog Bait (chlorophacinone 0.005%) is registered to control black‐tailed prairie dogs in ten states throughout the midwestern and western United States. RESULTS: We fed Rozol Prairie Dog Bait to captive black‐tailed prairie dogs for 2 days and analyzed their livers and whole bodies (without livers) for chlorophacinone residue on days 3, 5, 7, 9, 11, 14, 18 and 27 post‐exposure. We found the greatest levels of residues in livers ( x ‾ = 5.499 mg kg −1 ) and whole bodies ( x ‾ = 1.281 mg kg −1 ) on day 3. Residues in both tissues declined rapidly over time, with estimated half‐lives of approximately 6 days post‐exposure. However, a risk assessment of secondary toxicity to non‐target mammals indicated acute risks for mammalian species up to 27 days post‐exposure and negligible risks for birds. CONCLUSION: The results suggest that the greatest risk of secondary toxicity occurs ≤14 days post‐application of Rozol Prairie Dog Bait and declines thereafter. This corresponds to the time when chlorophacinone residues are high, and prairie dogs exhibit signs of intoxication and are perhaps most susceptible to predation and scavenging. These results confirm that Rozol Prairie Dog Bait should not be used in areas where black‐footed ferrets or other sensitive species occur. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.